A Study on Using Fluidized Bed Reactor for Treating Sanitary Sewage - Khudhair, Kifah M.; Gatea, Mudhar H. (Basrah Journal for Engineering Sciences, 2016)
Fluidized bed reactor (FBR) is an attached growth system used mainly for biological treatment of industrial wastewater of high organic content. These wastewaters are usually resulted from refineries and milk, starch, and olive oil industries. The objective of this study is to investigate the use of fluidized bed reactor for treating sanitary sewage. The study was accomplished using a pilot plant of the FBR. The pilot plant was constructed and installed in Hamdan Sewage Treatment Plant in Basrah governorate. That was to maintain continuous source of settled sewage which is the influent to the FBR. The period of plant operation was nine weeks. During, this period, the plant was operated at three phases of different conditions (up flow velocity and recirculation ratio). To study the performance of FBR, the main measured parameters were; BOD, DO, VSS, pH, and temperature. The most important conclusions of this study are; (1) the maximum efficiency of BOD removal is 78.6% which was obtained for hydraulic retention time (HRT) of 24min and upflow velocity of 1.59m/min, (2) the effluent BOD values during phases-1 and 2 of plant operation match that of stabilization ponds and trickling filters and during phase-3 matches that activated sludge process, (3) during all operation phases, the values of effluent pH are within the limits specified in national standards of secondary effluents, (4) as F/M increases, the efficiency of BOD removal decreases and the maximum efficiency of BOD removal (78.6%) was obtained at F/M ratio equals 23.47 day -1 , and (5) the HRT of fluidized bed reactor is on order of minutes, while, the values of HRT of activated sludge systems and stabilization ponds are on order of hours and days, respectively.